Voluntary Saccade Training Protocol in Persons With Parkinson’s Disease and Healthy Adults - Camacho, Paul B.; Carbonari, Ronald; Shen, Sa; Zadikoff, Cindy; Kramer, Arthur F.; López-Ortiz, Citlali (Frontiers in Aging Neuroscience, 2019)
1 Background: Voluntary saccade function gradually decreases during both the progression of Parkinson’s disease (PD) and neurologically healthy adult aging. Voluntary saccades display decreased length and increased saccade latency, duration, and the number of compensatory saccades in aging and PD. Saccades serve as the key eye movement for maintaining salient features of the visual environment on the high visual acuity fovea of the retina. Abnormal saccade behavior has been associated with freezing of gait in PD. We have not identified any studies that have investigated improvement in voluntary saccade function using voluntary saccade training. 2 Objective: We report an experimental protocol that tests a training paradigm following the principle of specificity to improve voluntary saccade velocity and amplitude, while decreasing latency and the number of compensatory saccades. 3 Methods: Persons with PD (n = 22) and persons with no known neurological disorders (n = 22) between the ages of 40 and 65 years will be recruited. In a randomized-block study design, all participants will perform voluntary saccades to targets in eight cardinal and intercardinal directions. In each of the eight sessions during the four-week intervention period, participants will train at three target amplitudes. Participants will perform 40 trials for each amplitude block, consisting of five randomly presented repetitions for each direction. Voluntary and reflexive saccades will be recorded pre- and post-intervention, along with clinical mobility assessment using the Movement Disorder Society Unified Parkinson’s Disease Rating Scale. Mobility scores, the amplitude, latency, and duration of the first saccade, and the number of saccades to reach the fixation target will be analyzed using an ANOVA of mixed effects. 4 Discussion: This protocol holds promise as a potential method to improve voluntary saccade function in persons with PD. Should persons with PD not improve on any outcome following the intervention, this lack of response may support the use of saccade assessment as a response biomarker for the diagnosis of PD. 5 Trial Registration: This protocol was retrospectively registered at ISRCTN (ISRCTN.com) since July 25, 2018. The first participant was recruited March 12, 2016. The protocol identifier is 17784042.